On a quiet street - Glass, Seraphina Nova (Graydon House, 2022)
"Cora thinks her husband, Finn, is cheating--she just needs to catch him in the act. That's where Paige comes in. Paige lost her son to a hit-and-run last year, and she's drowning in the kind of grief that makes people do reckless things like ... agreeing to Cora's plan to reveal what kind of man Finn really is. All the while, their reclusive new neighbor, Georgia, is acting more strangely every day. But what could such a lovely young mother possibly be hiding?"--